Adsorption behaviour of molecularly imprinted-beta-cyclodextrin polymers prepared by reversible addition-fragmentation chain transfer (RAFT) polymerization for selective recognition of benzylparaben - Asman, Saliza (2015)
Molecularly imprinted polymers (MIPs) are kinds of powerful materials with promising selective molecule recognition abilities. However, the conventional MIPs have relatively low binding capacity. In order to improve this characteristic of MIPs, the modification monomer based on β-cyclodextrin (β-CD) and the essential of reversible additionfragmentation chain transfer (RAFT) polymerization process were studied to generate potential MIPs. The study focuses on the characterization and adsorption behaviour of MIPs for selective recognition of benzylparaben (BzP) analyte. The potential of β-CD in MIP was investigated by synthesizing a reversible addition-fragmentation chain transfer molecularly imprinted methacrylic acid functionalized β-cyclodextrin polymer; RAFTMIP(MAA-β-CD) based on methacrylic acid functionalized β-cyclodextrin (MAA-β-CD) monomer, which was then compared to a reversible addition-fragmentation chain transfer molecularly imprinted methacrylic acid polymer; RAFT-MIP(MAA) synthesized without β-CD. Both MIPs were prepared by the RAFT polymerization process in bulk polymerization method. The resulting MIPs were characterized using Fourier Transform Infrared Spectroscopy (FTIR), Field Scanning Electron Microscope (FESEM) and Brunauer-Emmett-Teller (BET) analysis. The batch adsorption study that includes studying of the pH, kinetic, isotherm and thermodynamic was conducted. The essential of RAFT polymerization on MIP was studied by comparing RAFT-MIP(MAA-β-CD) with the molecularly imprinted methacrylic acid functionalized β-cyclodextrin polymer; MIP(MAA-β-CD) was synthesized without RAFT agent, and characterized by using FTIR, elemental analysis, FESEM and BET. The binding experiments demonstrated that the RAFT-MIP(MAA-β-CD) has a higher binding capacity and higher accessibility compared to RAFT-MIP(MAA) and MIP(MAA-β-CD) for selective of BzP, respectively. The β-CD and RAFT polymerization process improved the MIP’s physical properties and iv enhanced its recognition capacity, thus affecting the adsorption behaviour of RAFTMIP(MAA-β-CD). The effects of RAFT polymerization process were also investigated by a reversible addition-fragmentation transfer molecularly imprinted hydroxylethyl methacrylate functionalized β-cyclodextrin polymer; RAFT-MIP(HEMA-β-CD). The RAFT-MIP(HEMA-β-CD) was synthesized based on the hydroxylethyl-methacrylate functionalized β-cyclodextrin (HEMA-β-CD) monomer and was prepared by the RAFT polymerization process in bulk polymerization method. The molecularly imprinted hydroxylethyl-methacrylate functionalized β-cyclodextrin polymer; MIP(HEMA-β-CD) without a RAFT agent was synthesized as comparison. A similar study to RAFTMIP(MAA-β-CD) had also been carried out for RAFT-MIP(HEMA-β-CD).The effects of RAFT polymerization on RAFT-MIP(HEMA-β-CD) were contrasted with RAFTMIP(MAA-β-CD). The compact and non-porous morphology of RAFT-MIP(HEMA-βCD) reduces its binding capacity performance compared to MIP(HEMA-β-CD). Thus, this directly affected the RAFT-MIP(HEMA-β-CD) adsorption behaviour towards BzP. It was resulted that the RAFT polymerization had not improved the synthesis of RAFTMIP(HEMA-β-CD). Careful choice of RAFT agent and monomer is essential in realizing good control over the RAFT-MIP polymerization process, and generating potential MIP.